Digital Empathy and Bullying Awareness among Adolescents: A Quantitative Study in Bungo Regency - Karlinda Karlinda; Risty Afriyani; Frandes Frandes (Indonesian Journal of Global Health Research, 2025)
Generation Alpha adolescents are growing up in a digital ecosystem, making them highly vulnerable to the psychological impacts of social media, including cyberbullying. This study aims to explore the relationship between age, gender, digital empathy, and knowledge of bullying among adolescents in Bungo Regency. Using a quantitative design, data were collected from 150 junior high school students in Pasar Bungo through random sampling. The research data was collected in the form of a survey and pre-test and post-test questionnaires were administered to 150 junior high school students, then the data were analyzed in the form of descriptive and bivariate analysis using a correlation test to determine the strength and direction of the correlation of each variable. showed that 60% of respondents had good knowledge about bullying, yet only 48.7% had high digital empathy. Bivariate analysis revealed a moderately strong correlation between age and both bullying knowledge (r = 0.450) and digital empathy (r = 0.652). Female students showed stronger empathy and understanding of bullying behavior than males. These findings highlight the need to strengthen empathy-based digital education as a preventive approach to cyberbullying and to improve adolescent mental health.